High-density lipoprotein immunomodulates the functional activities of macrophage and cytokines produced during ex vivo macrophage-CD4+ T cell crosstalk at the recent-onset human type 1 diabetes. (August 2017) - Benghalem, Ibtissem; Meziane, Warda; Hadjidj, Zeyneb; Ysmail-Dahlouk, Lamia; Belamri, Ahmed; Mouhadjer, Kheira; Aribi, Mourad
Abstract: Background: Both CD4 + T cells and macrophages are mainly involved in the autoimmune-mediated β-cells destruction in type 1 diabetes (T1D). The aim of this study was to examine the effect of HDL on functional activities of macrophage and its ability to regulate the production of cytokines in autologous mixed macrophage/CD4 + T cells at the recent-onset human type 1 diabetes. Methods: Cell samples were isolated from volunteers with recent-onset T1D or healthy controls. Results: The levels of the production of IL-1β, IL-2, IFN-γ, nitric oxide (NO), and hydrogen peroxide (H2 O2 ) were significantly increased in the co-culture of T1D cells when compared to that of cells from healthy controls. Similarly, those of intracellular free calcium ions (if Ca 2+ ) were slightly, but not significantly increased ( p  > 0.05). Conversely, macrophage exhibited significantly decreased levels of the relative tyrosine phosphorylation of STAT6 (p-STAT6, Tyr641) in culture of T1D cells than in that of cells from healthy controls; while those of p-STAT4 (Tyr693) were significantly increased. Likewise, the levels of IL-4 and IL-10 were significantly decreased in the co-culture of T1D cells compared to co-culture of cells from healthy controls. Additionally, HDL treatment significantly down-regulated the production of IL-1β, IL-2, IFN-γ, NO, H2 O2, phagocytosis, bacterial killing, the relative tyrosine phosphorylation of macrophage-expressed STAT4 (p-STAT4, Tyr693), as well as the ratio of IL-1β/IL-10, NO production/arginase activity, p-STAT4/p-STAT6, IFN-γ/IL-4, IFN-γ/IL-10, and the combined proinflammatory (PICs)/anti-inflammatory (AICs) cytokines. Moreover, HDL treatment significantly up-regulated the production of IL-4, IL-10, arginase activity, and p-STAT6 (Tyr641) (for all comparisons, p  < 0.001). Conclusions: We show for the first time that HDL may reverse both the functional activities of macrophages and immunoinflammatory response during reciprocal macrophage-CD4 + T cell crosstalk at the beginning of T1D. These findings should open the way for therapeutic trials in the short- and medium-term.